International Migration, Transfers of Norms and Home Country Fertility - Beine, Michel; Docquier, Frederic; Schiff, Maurice (2012)
This paper examines the relationship between international migration and source country fertility. The impact of international migration on source country fertility may have a number of causes, including a transfer of destination countries' fertility norms and an incentive to acquire more education. It provides provide a rigorous test of the diffusion on of fertility norms using original and detailed data on migration. The results provide evidence of a significant transfer of fertility norms from migrants to their country of origin: a one percent decrease in the fertility norm to which migrants are exposed reduces home country fertility by about 0.3 percent for origin countries.